Separation between agricultural and forestry land - Ratknić, Mihailo; Rakonjac, Ljubinko; Veselinović, Milorad (Economics of Agriculture, 2010)
In the past two decades, the multidisciplinary research of land area has been current. The problem of these researches is exceptionally complex and it requires a disciplined and continuous work of different professionals (soil surveyors, geologists, soil scientists, phytocoenologists, climatologists, typologists, ecologists, statisticians, socio-demographers, economists, etc.) in the aim to fnd out and utilize the reliable parameters for the defnition of land area by quantity and quality. The fnal target is that such a defned land area is optimally utilized both from the social and from the economic aspects.